2015
DOI: 10.1371/journal.pone.0118667
|View full text |Cite
|
Sign up to set email alerts
|

Stridulatory Sound-Production and Its Function in Females of the Cicada Subpsaltria yangi

Abstract: Acoustic behavior plays a crucial role in many aspects of cicada biology, such as reproduction and intrasexual competition. Although female sound production has been reported in some cicada species, acoustic behavior of female cicadas has received little attention. In cicada Subpsaltria yangi, the females possess a pair of unusually well-developed stridulatory organs. Here, sound production and its function in females of this remarkable cicada species were investigated. We revealed that the females could produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…This rare species was originally reported from the foothills of the Qinling Mountains [33]. It was thought to be extinct after intensive field investigations in recent decades [36]. After the discovery of a population of S. yangi from the Helan Mountains in June 2011, a few more populations were discovered using our special acoustic playback method [35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This rare species was originally reported from the foothills of the Qinling Mountains [33]. It was thought to be extinct after intensive field investigations in recent decades [36]. After the discovery of a population of S. yangi from the Helan Mountains in June 2011, a few more populations were discovered using our special acoustic playback method [35].…”
Section: Discussionmentioning
confidence: 99%
“…Tainaka et al [101] illustrated that frequent speciation or extinction may occur in communities undergoing rapid environmental change. Habitat fragmentation and destruction of host-plants by human activities, particularly agricultural practices, is a critical threat to populations of S. yangi [36]. Therefore, assessment of habitat conditions and conservation needs of this rare species should be conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outside of birds, female sound production has been found in a diverse range of taxa, e.g. cicadas (Luo and Wei 2015), frogs (Roy 1997;Emerson and Boyd 1999), various monkey species (Sekulic 1983;Geissmann 2002;Townsend et al 2008), elk bugles (Feighny et al 2006), and fish (Ladich and Schleinzer 2020;Liesch and Ladich 2020).…”
Section: Introductionmentioning
confidence: 99%
“…When a higher concentration of odor is detected on one side of the antenna, the insect will rotate in the same direction, otherwise, it will turn to the other side. According to this simple principle, cicada can effectively find food [25][26]. With the continuous deepening of the experiment, we found that the performance of the CSO algorithm in dealing with high-dimensional functions is not very satisfactory, and the iterative result is very dependent on the initial position of the cockroach.…”
Section: Cicada Swarm Optimization Methods (Ciso)mentioning
confidence: 99%